Improvement of oil production in low permeability deposits with a system of horizontal wells - Krivova, N. R. (Revista de la Universidad del Zulia, 2020)
The article describes an approach to the production of difficult to extract oil, confined to deposits with low poroperm properties, using a system of horizontal wells and hydraulic multistage fracturing. The main problems that arise during the development of the well are analyzed. A conclusion is reached on the possibility of continuing to apply the method based on the analysis of pilot tests.